Discussion about the Legal Identity of Central and Eastern Europe. 3rd Annual CEENELS Conference “Legal Identities and Legal Traditions in CEE” - Szymaniec, Piotr (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The paper describes the discussions during the 3rd Annual CEENELS Conference “Legal Identities and Legal Traditions in CEE”, which took place on January 11–13, 2018 at the University of Latvia in Riga. The main issue debated at the conference concerned the question whether the countries of Central and Eastern Europe have their own legal identity and whether there is a common legal identity of the entire region. The author is in favor of Mikhail Antonov’s view that labeling the Soviet legal theory and legal culture as characterized by rigid positivism or even by “hyperpositivism” is an oversimplification. Moreover, Antonov is right when emphasizing that there was no common “socialist legal culture” and this culture differed a bit from country to country.